(untitled) (Journal of Environment Sciences, 2025)
Access to safe and clean drinking water is recognized as a fundamental human right. Kathmandu faces a number of problems in drinking water distribution, packaging and its availability. Human right assures for safe drinking water for healthy and prosperous life. This research aimed to compare drinking water quality of bottled and jar water in Kathmandu Valley on which most people are dependent on. 15 samples of each bottled water and jar water were collected from Kathmandu Valley. Both the physico-chemical and bacteriological parameters were analyzed. The physico-chemical parameters of bottled and jar water were compared statistically. Weighted arithmetic water quality index (WQI) method was used to oversee the quality of the water samples providing weightage to each parameter based on their standard value provided by National Drinking Water Quality Standards (NDWQS). Seven samples from bottled water and three samples from jar water had iron concentration greater than the maximum permissible limit set by NDWQS. Similarly, five samples from bottled water had pH value less than 6.5. Most Probable Number (MPN) test indicated all samples to be free from microbial contamination. There were significant differences between bottled water and jar water in terms of temperature, pH, ammonia, phosphate and iron (p<0.05). Among the measured parameters, pH, iron, and ammonia were found to be key contributors influencing the WQI, highlighting their value deviation from standard value. Majority of the samples from bottled water did not comply with the standards with respect to pH and iron concentration. The WQI assessment and bacteriological test indicated that all sampled waters were of good quality for drinking purposes. However, regular monitoring is recommended to ensure the continued safety and quality of drinking water in Kathmandu.